Identification and characterization of a cold-adapted and halotolerant nitrobenzene-degrading bacterium. Issue 98 (23rd October 2015) - Ma, Xiping; Li, Xianzhu; Li, Wanlong; Wang, Di; Xu, Chengbin; Meng, Xuelian
<x xml:space="preserve">Abstract</x> According to strain X7's morphological, physiological and biochemical characteristics and 16S rDNA gene sequence, the result showed that strain X7 was Myroides odoratus.